9.) Answer: B. f(x) = 4 - x
Explanation/Proof:
If we substitute, the answers are correct.
f(x) = 4 - (1)
f(x) = 3 ✅
f(x) = 4 - (2)
f(x) = 2 ✅
And so on and so forth.
10 because it makes the most sense
<span>Two algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.</span>
Answer:
The remaining solution to the equation is x = 1
Step-by-step explanation:
2x^2 + x - 1 = 2
First set the equation to zero by subtracting 2 from each side:
2x^2 + x - 1 - 2 = 2 - 2
2x^2 + x - 3 = 0
Factor the left side of the equation:
2x^2 + x - 3 = 0
(2x + 3)(x - 1) = 0
Now set each factor to zero and solve:
2x+ 3 = 0
2x+ 3 - 3 = 0 - 3
2x= -3
2x/2= -3/2
x= -3/2 (The given expression)
x - 1 = 0
x - 1 + 1 = 0 + 1
x = 1
Since we already knew x = -3/2, the missing solution is x = 1.
The value in the 10 digits place is 6, because the tenths place is like a centimeter, and the digit in the hundreds place, is 6 again, because it is 10 times greater than the tenths place.